2006
DOI: 10.1007/s10750-006-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Cook book for the development of a Multimetric Index for biological condition of aquatic ecosystems: Experiences from the European AQEM and STAR projects and related initiatives

Abstract: The requirements of the European Water Framework Directive (WFD), aimed at an integrative assessment methodology for evaluating the ecological status of water bodies are frequently being achieved through multimetric techniques, i.e. by combining several indices, which address different stressors or different components of the biocoenosis. This document suggests a normative methodology for the development and application of Multimetric Indices as a tool with which to evaluate the ecological status of running wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(122 citation statements)
references
References 28 publications
0
107
0
8
Order By: Relevance
“…However, our results from clearwater lakes demonstrated that although several of the metrics included in the MILA index show significant response to acidification, the MILA index itself did not. Generally, a multimetric index should only include metrics showing a quantitative dose-response change across a stressor gradient that is reliable, interpretable and not dispersed or obscured by natural variation (Hering et al 2004). In addition, the MILA approach does not take different sensitivity among closely related taxa into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results from clearwater lakes demonstrated that although several of the metrics included in the MILA index show significant response to acidification, the MILA index itself did not. Generally, a multimetric index should only include metrics showing a quantitative dose-response change across a stressor gradient that is reliable, interpretable and not dispersed or obscured by natural variation (Hering et al 2004). In addition, the MILA approach does not take different sensitivity among closely related taxa into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Na construção de índices multimétricos, Hering et al (2006) sugerem que a seleção das métricas centrais deve considerar apenas variáveis não correlacionadas entre si, para evitar redundância das informações nos valores finais dos índices. Para as comunidades de macroinvertebrados, quase todos os indicadores apresentaram correlações significativas entre si (Tabela 4).…”
Section: Resultsunclassified
“…Os riachos estudados representavam um gradiente de impactos por atividades rurais, incluindo não apenas as categorias extremas como também os níveis intermediários, possivelmente resultando na correlação entre as variáveis estudadas. De fato, a amostragem dos níveis intermediários de estresse ambiental é fortemente recomendada por Hering et al (2006) na construção de índices multimétricos. Além disso, no desenvolvimento dos índices, os riachos considerados impactados estavam sujeitos a diferentes condutores de degradação.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Community structure-based assessment models such as multimetric indices (MMIs) are typically calibrated within states or regions, but some models have been developed nationally (e.g., Stoddard et al 2008) and continentally (e.g., Hering et al 2006). For decades, benthic macroinvertebrates have served as excellent indicators of biological health in flowing waters (Resh and Jackson 1993); they are the most widely studied group and are typically considered one of the most sensitive to anthropogenic disturbance.…”
Section: Introductionmentioning
confidence: 99%